A bibliometric analysis of literature on engineering research among BRIC countries. (1st October 2018) - Elango, Bakthavachalam
Abstract : Purpose: The purpose of this paper is to make a quantitative analysis and compare the scientific productivity in the area of engineering among the BRIC (Brazil, Russia, India and China) countries. Design/methodology/approach: The data were collected from SCImago. Various parameters such as number of articles and citable articles, world share and rank, citations per paper and h-index, and international collaboration were analyzed. Findings: There was a fluctuation trend in the pattern of international collaboration among the BRIC countries during the period. Among the top countries, China ranked first in the world in terms of number of articles in the field of engineering research, whereas India was at the 8th rank, Russia was at the 12th rank and Brazil was at the 18th rank. Among the BRIC countries, Russia slipped three positions from being at the 7th rank in 1996 to being at the 10th rank in 2016, while others improved their ranks. Originality/value: The results of this study reveal publication trends and collaboration pattern of BRIC countries in the field of engineering which may be useful for the academic fraternity and decision makers.